2020
DOI: 10.1186/s40663-020-00273-w
|View full text |Cite
|
Sign up to set email alerts
|

The relationships among structure variables of larch forests in China

Abstract: Background Larch (Larix Mill.) forests are widely distributed in the upper parts of mountainous areas in China, playing vital roles in constructing mountain landscapes and maintaining mountain environments. Despite their importance, our knowledges on the large-scale patterns of structure characteristics and the relationships between different structure variables are unclear. In this paper, we investigated 155 plots from 11 natural larch forest types across the country to explore the biogeograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…6 and Table S4 ). In this analysis, in addition to environmental distance, larch forest type (identified by dominant larch species in the forest) also reflected the results of species niche differentiation since the distribution of different larch forest types in China has distinct zonality formed by a lengthy historical process ( Liu et al., 2002 ; Sundaram et al., 2019 , 2021 ; Fang et al., 2020 , 2022 ). Our results showed that larch forest types significantly affect total beta-diversity and the species turnover component of larch forests ( Table 2 ).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…6 and Table S4 ). In this analysis, in addition to environmental distance, larch forest type (identified by dominant larch species in the forest) also reflected the results of species niche differentiation since the distribution of different larch forest types in China has distinct zonality formed by a lengthy historical process ( Liu et al., 2002 ; Sundaram et al., 2019 , 2021 ; Fang et al., 2020 , 2022 ). Our results showed that larch forest types significantly affect total beta-diversity and the species turnover component of larch forests ( Table 2 ).…”
Section: Discussionmentioning
confidence: 84%
“…The tree layer of larch forests largely consists of coniferous species with less species richness. The understory species of these forests are relatively abundant because the transmittance of larch forests is relatively high and provides favorable light conditions for understory plants ( Fang et al., 2019 , 2020 ). We found beta-diversity was lower in trees than in shrubs and herbs growing at similar geographic or climatic distances ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Larch, as a typical softwood species, is mainly composed of one cell type (tracheid) with a uniform microtubule channel structure (Fig. 1a and 3a), 19 which contributes to shortening the transport routes for electrolyte ions as an ''electron expressway'' in the vertical direction. Generally, lignin and hemicellulose are embedded between the cellulose microfibers, and delignification can decompose lignin and hemicellulose to form more gaps of different sizes while preserving the microtubule channel structure of natural wood (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Larch, as the main fast-growing wood species for forest regeneration and afforestation, has abundant accumulation and stable construction. 10 It is widely used in housing construction, civil engineering, wood processing and other industries. A large amount of waste larch wood is produced during the harvesting and processing of larch.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, plantations such as Larix gmelinii (Ruprecht) Kuzeneva located in this study area should be included in the research scope, not only because of its wide distribution range and its in uence on the ecosystem that cannot be ignored but also because of its the function of landscape construction in a mountainous area (Fang et al 2020). However, this is poorly understood in the scienti c literature.…”
Section: Introductionmentioning
confidence: 99%